2022
DOI: 10.1177/17562848221074188
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of golimumab in patients with ulcerative colitis: results of a real-life study in Switzerland

Abstract: Background: Tumor necrosis factor (TNF) inhibitors have improved treatment of ulcerative colitis (UC), but loss of response remains a frequent problem. The anti-TNF agent, golimumab, was approved in Switzerland for the treatment of UC in 2014. This study aims to summarize the experience of golimumab in a real-world setting in Switzerland. Methods: We analyzed real-world data from 1769 UC patients from the Swiss Inflammatory Bowel Disease Cohort (SIBDC) study and performed a chart review of golimumab-treated pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…This patient population difference may explain, at least in part, the higher induction response rate in PURSUIT-SC compared with GO OBSERVE, as it is well established that UC patients with previous exposure to biological therapy have been shown to be less responsive to biological therapy. The induction response rate observed in the present study was within the range of induction response rates reported in previous real-world studies with GLM in UC [9–13].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This patient population difference may explain, at least in part, the higher induction response rate in PURSUIT-SC compared with GO OBSERVE, as it is well established that UC patients with previous exposure to biological therapy have been shown to be less responsive to biological therapy. The induction response rate observed in the present study was within the range of induction response rates reported in previous real-world studies with GLM in UC [9–13].…”
Section: Discussionsupporting
confidence: 89%
“…within the range of induction response rates reported in previous real-world studies with GLM in UC [9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 79%
“…In addition, GLM persistence rates at 1 and 2 years after initiation were 54.5% and 45.4%, respectively. Other real-world cohort studies of GLM reported that the treatment persistence rates ranged from 44.7% to 63% at 1 year [ 8 , 11 , 15 17 , 20 , 23 ] and 22.5–46% at 2 years [ 15 , 16 ]. Thus, the persistence rates of GLM in Japanese patients with UC have a similar tendency to that reported in a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…GLM is a subcutaneously administered fully human anti-tumor necrosis factor-α (TNF-α) antibody. Several clinical trials [2,3] and real-world data [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] outside Japan have demonstrated the clinical efficacy and safety of GLM in induction and maintenance therapy in patients with moderate-to-severe active UC. In addition, the PURSUIT-J study showed that GLM treatment for 54 weeks maintained clinical efficacy and safety through week 54 among induction responders in biologic-naïve Japanese patients with moderate-to-severe active UC [22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, switchers/swappers and those who experienced ADRs were associated with a higher risk of non-persistence: 33% of patients switched to another biologic at least once, especially patients treated with anti-TNFα, as observed in other studies [ 28 , 42 , 43 ]. The treatment failures were mainly reported for GOL, which consistently remained the least frequently used anti-TNFα drug in UC and was used more frequently as a second- and third-line therapy [ 44 ]. Recent studies confirm that UC patients treated with GOL after previous failure of other anti-TNFα drugs had significantly worse outcomes [ 45 , 46 ], whereas the use of the i.v.…”
Section: Discussionmentioning
confidence: 99%